PICCA study: panitumumab in combination with cisplatin/gemcitabine chemotherapy in KRAS wild-type patients with biliary cancer—a randomised biomarker-driven clinical phase II AIO study. (March 2018) - Vogel, Arndt; Kasper, Stefan; Bitzer, Michael; Block, Andreas; Sinn, Marianne; Schulze-Bergkamen, Henning; Moehler, Markus; Pfarr, Nicole; Endris, Volker; Goeppert, Benjamin; Merx, Kirsten; Schnoy, Elisabeth; et al.
Abstract: Background: Combination chemotherapy has shown benefit in the treatment of biliary cancer and further improvements might be achieved by the addition of a biological agent. We report here the effect of chemotherapy with the monoclonal EGFR antibody panitumumab as therapy for KRAS wild-type biliary cancer. Patients and methods: Patients with advanced biliary tract cancer were randomised (2:1) to receive cisplatin 25 mg/m 2 and gemcitabine 1000 mg/m 2 on day 1 and day 8/q3w with (arm A) or without panitumumab (arm B; 9 mg/kg BW, i.v q3w). The primary end-point was the evaluation of progression-free survival (PFS) at 6 months. Secondary end-points included objective response rate (ORR), overall survival (OS), and toxicity. In addition, a post hoc assessment of genetic alterations was performed. Finally, we performed a meta-analysis of trials with chemotherapy with and without EGFR antibodies. Results: Sixty-two patients were randomised in arm A and 28 patients in arm B. Patients received 7 treatment cycles in median (1–35) with a median treatment duration of 4.7 months (141 days, 8–765). PFS rate at 6 months was 54% in patients treated with cisplatin/gemcitabine and panitumumab but was 73% in patients treated with cisplatin/gemcitabine without antibody, respectively. Secondary end-points were an ORR of 45% in treatment arm A compared with 39% receiving treatment B and a median OS of 12.8 months (arm A) and of 20.1 months (arm B), respectively. In contrast to the p53-status, genetic alterations in IDH1/2 were linked to a high response after chemotherapy and prolonged survival. In accordance with our results, the meta-analysis of 12 trials did not reveal a survival advantage for patients treated with EGFR antibodies compared with chemotherapy alone. Conclusions: Panitumumab in combination with chemotherapy does not improve ORR, PFS and OS in patients with KRAS wild-type, advanced biliary cancer. Genetic profiling should be included in CCA trials to identify and validate predictive and prognostic biomarkers. Clinical Trials Number: The trial was registered withNCT01320254 . Highlights: Panitumumab was evaluated in KRAS wild-type patients with biliary cancer. Addition of EGFR antibody to standard chemotherapy does not improve outcome of patients. Molecular profiling identified p53 and IDH1/2 mutation as most common genetic alteration in our patient population. IDH1/2 mutations might predict benefit from platin-based chemotherapy, which should be explored in prospective trials.